2019
DOI: 10.1111/jcmm.14404
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐34b‐3p represses cell proliferation, cell cycle progression and cell apoptosis in non‐small‐cell lung cancer (NSCLC) by targeting CDK4

Abstract: Lung cancer is the most common incident cancer, with a high mortality worldwide, and non‐small‐cell lung cancer (NSCLC) accounts for approximately 85% of cases. Numerous studies have shown that the aberrant expression of microRNAs (miRNAs) is associated with the development and progression of cancers. However, the clinical significance and biological roles of most miRNAs in NSCLC remain elusive. In this study, we identified a novel miRNA, miR‐34b‐3p, that suppressed NSCLC cell growth and investigated the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…44 This study found that ICIs induced the accumulation of miR-34a-5p in the exosomes and its transfer to cardiomyocytes, thus leading to cardiac senescence. miR-34 has been reported to promote cell cycle arrest, 45 coincident with the finding of the present study that exosomal-delivered miR-34a-5p inhibited cell cycle in the G0/G1 phase. miR-34a triggers senescence partly through the genetic inhibition of PNUTS in cardiomyocytes.…”
Section: Open Accesssupporting
confidence: 92%
“…44 This study found that ICIs induced the accumulation of miR-34a-5p in the exosomes and its transfer to cardiomyocytes, thus leading to cardiac senescence. miR-34 has been reported to promote cell cycle arrest, 45 coincident with the finding of the present study that exosomal-delivered miR-34a-5p inhibited cell cycle in the G0/G1 phase. miR-34a triggers senescence partly through the genetic inhibition of PNUTS in cardiomyocytes.…”
Section: Open Accesssupporting
confidence: 92%
“…For example, downregulated miR-545 expression in NSCLC enhances expressions of CDK4 leading to enhanced cell proliferation [146]. Similarly, other tumor suppressive miRNAs including miR-486-5p [147], miR-613 [148], miR-340 [149], and miR-34b-3p [150] upregulate expression of CDK4 in NSCLC. Although few studies of non-coding RNAs involved in the immortalization process have been demonstrated in lung cancer, the aforementioned data suggests that these links could provide valuable therapeutic targets.…”
Section: Role Of Non-coding Rnas In Immortalized Genesmentioning
confidence: 99%
“…Feng and colleagues reported that miR‐34b exhibited a repressive effect on NSCLC cell proliferation and promotion effect on cell apoptosis . MiRNAs have drawn great attention to the diagnosis, prognosis and metastasis of tumors. Here, in our study, miR‐148b expression was found to be downregulated in NSCLC and was closely associated with clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, upregulation of miR‐221, −21, −421 were found in NSCLC and participated in the proliferation, metastasis and apoptosis as oncogenes. Moreover, downregulation of miR‐612, −621, −34b have been proven to be associated with the development of NSCLC . Wang et al .…”
Section: Introductionmentioning
confidence: 99%